The Solution of Social Problems among Vocational Students in Johor, Malaysia - Bekri Rahim, Mohd; Sumarwati, Sri; Anuar Abdul Rahman, Khairul; Kamis, Arasinah; Afiat Jalil, Siti (International Journal of Psychosocial Rehabilitation, 2020)
The social problems that occur among vocational students need to be restored to ensure the country's ability to cope with IR4.0. Therefore, this study is conducted to identify the types of social problems that occur frequently and to investigate the solution of social problems among vocational students in Johor, Malaysia. This study has been using descriptive quantitative methods using questionnaires as a research instrument. The results of a pilot study of 31 counseling teachers found that there were four items with a Cronbach's alpha value of less than 0.7. Therefore, only 41 items had a Cronbach's alpha value greater than 0.7, which means that items' were valid and reliable for obtaining study data. Respondents consist of 70 counseling teachers who teach at vocational colleges in Johor. The results of the study found that social problems often occur among vocational students who are fighting and vandalizing. The appropriate solution for punishment, namely, provides warning and counseling. Besides, a solution to social problems for motivation is provided, i.e., individual counseling. The solution for spiritual advice is joint congregational prayers and community service activities. The results of this research also showed that there is no significant difference in the solution of social problems based on teacher gender. Through the findings of this study, it can be a reference for school teachers to identify effective measures to address the social problems that occur among vocational students. The results of this study are expected to be a guide and information for the Ministry of Education Malaysia to identify and take action to solve the social problems that occur among vocational students.